Analysis of the World Scientific Production on the Topic of Industry 4.0 From 1990 to 2020 - Teixeira de Souza, Marina; Almada Santos, Fernando César (Revista Gestão da Produção Operações e Sistemas, 2021)
Objective – This study aims to analyze the scientific production on the topic of Industry 4.0. Theoretical framework – The work presented a literary review about the concept, how Industry 4.0. has developed and its characteristics. Design/methodology/approach – The methodology proposed for this work is based on bibliographic research and the application of bibliometric procedures. Findings – Eight hundred and fifty articles were found up to 2020. The publications involved 2,625 authors, from 75 countries, 1,084 institutions and 201 different journals. Highlighting that 88.3% of the articles were published in the last three years. The countries that stood out the most were China and Italy, and the most prolific journal was Applied Sciences Basel, with 59 articles. The most cited article received 343 citations and the largest production per author was nine articles. The topic has risen significantly in recent years with empirical and theoretical studies. Research, Practical & Social implications – The topic is of exponential interest for academics, researchers and managers and for directly impacting business models and organizational strategies, the study involved presenting the development and trends, in an orderly manner, of Industry 4.0 in the period from 1990 to 2020. Originality/value – The originality of the study comes from the gap identified, which corresponds to the need for a bibliometric study that presented the main countries, years of publications, most cited and most published authors, periodicals and recurring keywords, in addition to identifying developments and trends in this topic. Keywords – Industry 4.0. Fourth Industrial Revolution. Trends.